Multiple cystic brain infection: a diagnostic dilemma of neurocysticercosis and intracranial tuberculoma - Chew, Jia Xin; Tan, Juen Kiem; Cheong, Xiong Khee; Ho, Wen Chung; Mohamed Arifin, Noorasyikin; Chinnasami, Suganthi; Md Arif, Md Hanif; Kah Chuan, Lim; Kamaludeen, Shaharudeen (Springer Science and Business Media LLC, 2024)
Neurocysticercosis (NCC) is a central nervous system infection caused by Taenia solium or pork tapeworm. It affects millions worldwide and represents a leading cause of epilepsy in developing countries. NCC may be challenging to distinguish from intracranial tuberculomas, with tuberculosis being highly prevalent in developing countries. We highlight the importance of clinical history, including exposure history and neuroimaging, in obtaining an accurate diagnosis to enable prompt treatment. This report presents the case of a 26-year-old man diagnosed with NCC and presenting with acute giddiness and headache. Otherwise, there was no history of fever or constitutional symptoms. Neuroimaging demonstrated multiple cerebral lesions over both hemispheres, with degenerating scolex on brain MRI. He recovered well following a combination of oral albendazole, praziquantel, and corticosteroids. This case highlights the salient features that distinguish NCC from intracranial tuberculoma. Early and precise diagnosis will ensure that patients receive optimal treatment, expedite recovery, and prevent further complications.